Gender-Role Stereotypes in the Bulgarian Family: Cross-Generational Transmission of Gender Attitudes - Manol Nikolov Manolov; Ivan Kirilov Ivanov; Velislava Atanasova Chavdarova (Societies, 2023)
This article reports a representative quantitative and qualitative study covering the entire territory of Bulgaria, related to the analysis of stereotypes regarding male and female roles in the family and in the society. The results of the study indicate that the factor “age” is significant in relation to attitudes towards the social roles of men and women in the modern family, including in relation to domestic violence. The interpretation of the results enabled the formulation of justified conclusions related to changes in attitudes towards the roles of men and women in a dynamic way. The hypothesis was proven that the tensions between them can be more easily overcome through appropriate differentiated measures tailored to the different age groups.